2018
DOI: 10.1016/j.ijrobp.2018.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging of Pathologic Response to Chemoradiation in Esophageal Cancer

Abstract: Quantitative volume ΔADC and TLG during treatment may serve as early imaging biomarkers for discriminating pathologic response to chemoradiation in esophageal cancer. Validation of these data in larger, prospective, multicenter studies is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 20 publications
3
57
1
Order By: Relevance
“…Furthermore, an increase in ADC after nCRT compared with the baseline value seemed to be predictive of gross tumour response, defined as TRG 1–2 or TRG 1–3. However, the results reported for the preoperative selection of complete response (TRG 1 only) using ADC values were poor. In contrast, in the present study, preoperative visual response assessment on DW‐MRI after nCRT had high sensitivity for the detection of residual tumour.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Furthermore, an increase in ADC after nCRT compared with the baseline value seemed to be predictive of gross tumour response, defined as TRG 1–2 or TRG 1–3. However, the results reported for the preoperative selection of complete response (TRG 1 only) using ADC values were poor. In contrast, in the present study, preoperative visual response assessment on DW‐MRI after nCRT had high sensitivity for the detection of residual tumour.…”
Section: Discussioncontrasting
confidence: 66%
“…The present study evaluated oesophageal MRI for the assessment of complete response of the primary tumour by visual interpretation of morphology on T2W‐MRI and restrictive signals on DW‐MRI. Previous studies on this subject did not perform visual assessment, but focused on quantitative DW‐MRI. These studies found that an increase in the apparent diffusion coefficient (ADC, a quantitative measure of the magnitude of diffusion) during nCRT, compared with before nCRT, is a predictor of response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI scans were performed on a field strength of 1.5 Tesla in nine studies [45][46][47][48][49][50][51][52][53]. 3.0 Tesla MRI scanners were used in four studies [54][55][56][57]. One study did not report on the field strength used [58].…”
Section: General Study Characteristicsmentioning
confidence: 99%
“…The risk of bias regarding patient selection was high in one study, which only included cT4 tumours [47]. Patient selection was scored unclear if an inclusion period and inclusion number were reported without explaining potential exclusions from analyses [45,50,[54][55][56].…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%